Enantioseparation of penconazole, myclobutanil and triadimefon by cyclodextrin-modified micellar electrokinetic chromatography - Wan Ibrahim, Wan Aini; Hermawan, Dadan; Sanagi, Mohd. Marsin (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
Simultaneous enantioseparation of three chiral triazole fungicides i.e. penconazole, myclobutanil and triadimefon by cyclodextrin-modified micellar electrokinetic chromatography (CD-MEKC) under acidic condition was investigated with different HP-?-CD concentrations as chiral selector. The three triazole fungicides have an asymmetrically substituted carbon atom respectively, and they all contain two enantiomers. In order to achieve the best enantioresolution of these triazole fungicides, the HP-?-CD concentration range was optimized from 0 to 40 mM in 10 mM increment. The results indicate that separation of enantiomers was not achieved with concentration range of HP-?-CD from 0 to 20 mM. Simultaneous enantioseparation was successfully achived at 30 mM and 40 mM HP-?-CD concentration in 25 mM phosphate buffer (pH 3.0) solution that containing 50 mM SDS, 10% methanol and 5% acetonitrile. However, enantioresolution decreased for myclobutanil and triadimefon enantiomers with HP-?-CD concentration greater than 30 mM. In addition, an increase in the concentration of HP-?-CD caused a significant increase in the analysis time. In light of these aspects, the optimal concentration for HP-?-CD was decided to be 30 mM for the simultaneous chiral separation of the three triazole fungicides with resolutions (Rs) between enantiomers for penconazole, Rs = 0.81; myclobutanil, Rs = 1.14; triadimefon, Rs = 2.09; peak efficiencies (N) greater than 108 000 for all stereoisomers and analysis time of less than 15 min